2008
DOI: 10.1177/1359105307088141
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy for Exercise in Cardiac Rehabilitation

Abstract: Despite the numerous physical and psychosocial benefits of exercise for coronary heart disease survivors, non-adherence to cardiac rehabilitation (CR) exercise is a major problem. Adherence to the lifestyle behavior change associated with CR involves both physical and self-regulatory skills. While self-regulatory efficacy is clearly linked to exercise adherence and adjustment, the literature on the relationship between self-efficacy and exercise among CR participants has not been systematically reviewed. A sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(98 citation statements)
references
References 62 publications
5
89
0
4
Order By: Relevance
“…In relation to models of behavioural change, prior studies have shown that techniques such as goal setting and feedback can be useful for developing self-efficacy, which refers to someone's confidence in being able to perform and control a behaviour [25]. Previous research has identified selfefficacy as an important predictor of exercise behaviour amongst patient and non-patient samples [30][31][32][33][34]. It may influence the activities people choose to engage in, the energy they put into these and the persistence they demonstrate in their execution [25].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In relation to models of behavioural change, prior studies have shown that techniques such as goal setting and feedback can be useful for developing self-efficacy, which refers to someone's confidence in being able to perform and control a behaviour [25]. Previous research has identified selfefficacy as an important predictor of exercise behaviour amongst patient and non-patient samples [30][31][32][33][34]. It may influence the activities people choose to engage in, the energy they put into these and the persistence they demonstrate in their execution [25].…”
Section: Discussionmentioning
confidence: 98%
“…It may also be helpful to base interventions on theories that have been associated with behaviour change, including those encompassing self-efficacy, such as Bandura's [25] Social Cognitive Theory. Exercise self-efficacy enhancement has started to be considered by researchers as an important variable to address amongst those with cardiovascular disease [34,36,37]. However, more investigation is required so that clearer advice can be provided about which theoretical frameworks are best for promoting physical activity amongst people with HF.…”
Section: Clinical and Research Implicationsmentioning
confidence: 98%
“…Si è così passati dai primi studi sul "Tipo A" [4,5,6], all'impatto degli stress psico-sociali [7,8,9,10], allo studio delle relazioni fra depressione e malattia cardiache [11,12,13,14,15], all'identificazione di fattori protettivi quali il supporto psico-sociale [16,17,18], fino a specificare quali modalità di reazione del paziente potessero favorirlo o meno nella gestione di un evento cardiaco quali l'autoefficacia [19,20,21,22] o le modalità di attribuzione causale come il locus of control [23,24,25].…”
Section: Introduzioneunclassified
“…Thus the first step in helping patients with cardiovascular disease is determining the factors that could influence the patients' adherence. There is a plenty of evidence to support that provision of information [2] [3], focusing on personal motivation to change unhealthy life habits [4] [5], autonomous regulation and self-efficacy [6] [7], and implementation of behavioral techniques [5] could enhance adherence in CHD patients. Therefore, patients should receive proper information, education and support to be able to change their lifestyles, and to maintain these changes, and comply with therapeutic interventions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Theory-driven interventions and studies of single theory clinical trials allow unambiguous examination of the entire theoretical models, and their efficiency to identify the factors that predict sustained behavioral changes [7] [13].…”
Section: Introductionmentioning
confidence: 99%